2013
DOI: 10.1097/pas.0b013e31828309c4
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study Directly Comparing the Diagnostic Accuracy of Gene Expression Profiling and Immunohistochemistry for Primary Site Identification in Metastatic Tumors

Abstract: Metastatic tumors with an uncertain primary site can be a difficult clinical problem. In tens of thousands of patients every year, no confident diagnosis is ever issued, making standard-of-care treatment impossible. Gene expression profiling (GEP) tests currently available to analyze these difficult-to-diagnose tumors have never been directly compared with the diagnostic standard of care, immunochemistry (IHC). This prospectively conducted, blinded, multicenter study compares the diagnostic accuracy of GEP wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 23 publications
4
62
1
2
Order By: Relevance
“…Consistent with previous studies (33)(34)(35), IHC screening was able to postulate probable primary sites in 59% (26/44) of confirmed CUP cases. Interestingly, the median survival of confirmed CUP patients with no probable primary site was higher than those with probable primary sites (figure 2).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Consistent with previous studies (33)(34)(35), IHC screening was able to postulate probable primary sites in 59% (26/44) of confirmed CUP cases. Interestingly, the median survival of confirmed CUP patients with no probable primary site was higher than those with probable primary sites (figure 2).…”
Section: Resultssupporting
confidence: 78%
“…The remaining half of our CUP patients underwent extensive investigations and primary sites were postulated in only 59% of those cases. In previous studies, IHC had similar rate of success in postulating the primary site (34,35). Therefore, the primary site could not be identified in a significant proportion of our CUP patients.…”
Section: Discussionmentioning
confidence: 99%
“…The Handorf study 29 also showed that performing additional rounds of IHC testing after a first round generally failed to provide additional diagnostic information. The panel thus recommends that only one round of staining (8-10 stains) be performed when IHC is used.…”
Section: Molecular Profilingmentioning
confidence: 99%
“…In a recent, blinded, multicenter study by Handorf et al, 29 the diagnostic accuracy of the 1550-gene GEP assay was compared with that of IHC staining in a set of metastases from known primaries. The results indicated that the accuracies were similar, with 89% accuracy for GEP and 83% accuracy for IHC (P=.013).…”
Section: Ihc Vs Gepmentioning
confidence: 99%
“…226 Pathway Diagnostics (now defunct) also reported high diagnostic accuracy in identification of tumors of uncertain origin using microarray methodology. 227 …”
Section: Molecular Profiling For Identificationmentioning
confidence: 99%